Coded Orthogonal Frequency Division Multiplexing System : An Overview - Farhan, Mhnd (Universitas Airlangga, 2024)
This article compares the performance of two modulation techniques”quadrature phase shift keying (QPSK) and M-ary quadrature amplitude modulation (M-QAM) with M=8, 16, 32, and 64”in a coded orthogonal frequency division multiplexing system. As an error-correcting code, convolutional technology is employed. A vehicular channel with additive white gaussian noise (AWGN) is utilized for communication. According to simulation data, for QPSK and M-QAM, a coded orthogonal frequency division multiplexing system performs better than an uncoded one. Additionally, the system performs better with QPSK than it does with M-QAM. Additionally, when M rises, the performance declines.